Graphene Foam Chemical Sensor System Based on Principal Component Analysis and Backpropagation Neural Network - Yue, Weiwei; Zhang, Zhen; Tang, Caiyan; Qin, Ge; Sun, Jinjin; Xie, Xiaohui; Hua, Hongling; Ding, Zhaoqiang (Advances in condensed matter physics, 2018)
A kind of graphene foam chemical sensor (GFCS) system based on the principal component analysis (PCA) and backpropagation neural network (BPNN) was presented in this paper. Compared with conventional chemical sensors, the GFCS could discriminate various chemical molecules with selectivity without surface modification. The GFCS system consisted of an unmodified graphene foam chemical sensor, an electrical resistance time domain detection system (ERTDS), and a pattern recognition module. The GFCS has been validated via several chemical molecules discrimination including chloroform, acetone, and ether. The experimental results showed that the discrimination accuracy for each molecule exceeded 97% and a single measurement can be achieved in ten minutes. This work may have presented a new strategy for research and application for graphene chemical sensors.